The Anthropology of Conservation NGOs Rethinking the Boundaries (Palgrave Studies in Anthropology of Sustainability, 2018)
This book explores how NGOs have been influential in shaping global biodiversity, conservation policy, and practice. It encapsulates a growing body of literature that has questioned the mandates, roles, and effectiveness of these organizations-and the critique of these critics. This volume seeks to nurture an open conversation about contemporary NGO practices through analysis and engagement.